Pandangan Filsafat Hedonisme tentang Pendidikan Moral - Ahmad Samawi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
Hedonism’s View of Moral Education. Hedonism believes in pleasure as the highest good and humankind’s proper or sole aim. Moral education which is based on this philosophy will result in learners who pursue satisfaction of desires or wishes or immediate physical-biological enjoyment and thus neglect the mental-spiritual aspects of the education as these aspects do not offer immediate satisfaction and physical-biological enjoyment. As a result, teachers and learners place heavy emphasis on educational activities which are concrete and useful for practical purposes in life.